2020
DOI: 10.1089/pancan.2020.0005
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Ribociclib Plus Everolimus in Patients with Metastatic Pancreatic Adenocarcinoma Refractory to Chemotherapy

Abstract: Purpose: Metastatic pancreatic adenocarcinoma (mPC) has a poor prognosis. CDK4/6 is often deregulated in mPC due to CDKN2A loss, resulting in the loss of p16INK4a that inhibits CDK4/6. CDK4/6 inhibitor monotherapy is ineffective due to RAS-mediated activation of alternative pathways, including phosphatidylinositol 3-kinasemammalian target of rapamycin (PI3K-mTOR). We conducted a phase I study combining CDK4/6 and mTOR inhibition in patients with mPC refractory to standard chemotherapy. Materials and Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…However, Wolpin et al demonstrated that daily everolimus administered as a single agent had little clinical efficacy in patients with gemcitabine-resistant PDAC (71). Similarly, the combination of everolimus with cytotoxic therapies (e.g., gemcitabine and cisplatin) also failed to achieve meaningful therapeutic responses in patients with PDAC (72)(73)(74). These results suggest that single-target therapy may not be sufficient for the eradication of pancreatic cancer cells, especially for refractory and chemoresistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wolpin et al demonstrated that daily everolimus administered as a single agent had little clinical efficacy in patients with gemcitabine-resistant PDAC (71). Similarly, the combination of everolimus with cytotoxic therapies (e.g., gemcitabine and cisplatin) also failed to achieve meaningful therapeutic responses in patients with PDAC (72)(73)(74). These results suggest that single-target therapy may not be sufficient for the eradication of pancreatic cancer cells, especially for refractory and chemoresistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In prospective trials of traditional chemotherapy, targeted therapy, and immunotherapy combinations, the mPFS in the second line ranged from 1.5 to 3.1 months. 9,[31][32][33][35][36][37]40,42,50 The mPFS achieved in the third line for SM-88 Regimen was 1.8 months versus an equivalent 1.8 months for ribociclib plus everolimus, 45 2.3 months for GVAX, and 2.1 months for chemotherapy. 43 We believe that our OS and PFS findings indicate a potential role for SM-88 Regimen in the second-line for patients with mPDAC, especially as the 920 mg dose appeared to be much more tolerable than traditional chemotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of grade 3 or higher adverse events was 40% in the olaparib group and 23% in the placebo group. Two studies targeting CDK4/6 inhibitors in combination with mTOR inhibitors or paclitaxel are ongoing in PDAC (32,33). Other studies targeting low-incidence, operable mutations are ongoing, some with relatively significant results (34,35).…”
Section: Discussionmentioning
confidence: 99%